Clinical profile of type 1 diabetes mellitus among children in eastern part of Nepal - Muktan, Dipak; Tamang Ghising, Lisa; Singh, Rupa Rajbhandari (International Journal of Contemporary Pediatrics, 2019)
Background: The objective of this study is to determine the clinical profile of Type 1 diabetes mellitus (T1DM) among children. Methods: Descriptive cross sectional study was conducted at B.P. Koirala institute of Health Sciences (BPKIHS), Dharan, Nepal, the eastern part of Nepal. A total of 42 diabetic children of less than 20 years old diagnosed with T1DM were included in the study. Data were collected via semi-structured interviews and medical records of patients attending diabetic clinic at the time of follow up. Results: The mean age at diagnosis of disease was 11.1±4.9 years. Polyuria 33 (78.6%) was found to be the commonest symptom followed by polydipsia 27 (64.3%), weight loss 23 (54.8%) and polyphagia 13 (30.9%). The mean duration of symptoms before diagnosis was 14.3±9.7 days. DKA was present in 25 (59.5%) children at the time of diagnosis. Mean Glycosylated hemoglobin (HbA1c) value was 10.6±2.7. Obesity was observed in 9 (21.4%) children. Nine (21.4%) children had family history of diabetes. In most of the cases, primary caregiver was mother, among them only 24 (57.2%) had formal education. Almost half of the caregivers were using FRIO, an insulin cooling case, for insulin storage. Conclusions: Polyuria was the most common presenting symptom followed by polydipsia, weight loss and polyphagia. Moreover, most of the children had landed up in diabetic keto-acidosis (DKA) at the time of diagnosis. Therefore, community awareness programs should be emphasized among parents and primary health care workers especially in rural areas regarding T1DM for early recognition and prompt treatment.